Cancer risk following lymphoid malignancies among HIV-infected people. (1st July 2020) - Mahale, Parag; Ugoji, Chinenye; Engels, Eric A.; Shiels, Meredith S.; Peprah, Sally; Morton, Lindsay M.
Abstract : Objective(s): HIV-infected people have increased cancer risk. Lymphoma survivors have an increased risk of certain second primary cancers in the general population, but second cancer risk among HIV-infected people is poorly understood. Herein, we characterized the risk of cancers following lymphoid malignancies among HIV-infected people. Design: Population-based linkage of HIV and cancer registries. Methods: We used data from the US HIV/AIDS Cancer Match Study (1996–2015) and evaluated the risk of first nonlymphoid malignancy in Cox regression models, with first lymphoid malignancy diagnosis as a time-dependent variable. Results: Among 531 460 HIV-infected people included in our study, 6513 first lymphoid and 18 944 first nonlymphoid malignancies were diagnosed. Risk of nonlymphoid cancer following a lymphoid malignancy was increased overall [adjusted hazard ratio (aHR) = 2.7; 95% confidence interval (CI) = 2.3--3.2], and specifically for cancers of the oral cavity (aHR = 2.6; 95% CI = 1.2–5.5), colon (2.4; 1.1–5.0), rectum (3.6; 1.9–6.7), anus (3.6; 2.5–5.1), liver (2.0; 1.2–3.5), lung (1.6; 1.1–2.4), vagina/vulva (6.1; 2.3–16.3), and central nervous system (5.0; 1.6–15.6), Kaposi sarcoma (4.6; 3.4–6.2), and myeloid malignancies (9.7; 6.1–15.4). After additional adjustment for prior AIDS diagnosis and time since HIV diagnosis, aHRs were attenuated overall (aHR = 1.7; 95% CI = 1.5–2.0) and remained significant for cancers of the rectum, anus, and vagina/vulva, Kaposi sarcoma, and myeloid malignancies. Conclusion: HIV–infected people with lymphoid malignancies have an increased risk of subsequent non–lymphoid cancers. As risks remained significant after adjustment for time since HIV diagnosis and prior AIDS diagnosis, it suggests that immunosuppression may explain some, but not all, of these risks. Abstract : Supplemental Digital Content is available in the text